The Potential Diagnostic and Prognostic Value of Circulating MicroRNAs in the Assessment of Patients With Prostate Cancer: Rational and Progress - Samami, Elham; Pourali, Ghazaleh; Arabpour, Mahla; Fanipakdel, Azar; Shahidsales, Soodabeh; Javadinia, Seyed Alireza; Hassanian, Seyed Mahdi; Mohammadparast, Saeid; Avan, Amir (Frontiers in Oncology, 2022)
Prostate cancer (PC) is one of the most frequent diagnosed cancers among men and the first leading cause of death with an annual incidence of 1.4 million worldwide. Prostate specific antigen is being used for screening/diagnosis of prostate disease, although it is associated with several limitations. Thus identification of novel biomarkers is warranted for diagnosis of patients at earlier stages. MicroRNAs (miRNAs) are recently being emerged as potential biomarkers. It has been shown that these small molecules can be circulated in body fluids and prognosticate the risk of developing PC. Several miRNAs, including MiR-20a, MiR-21, miR-375, miR-378, and miR-141; have been proposed to be expressed in prostate cancer. This review summarizes the current knowledge about possible molecular mechanisms and potential application of tissue specific and circulating microRNAs as diagnosis, prognosis and therapeutic targets in prostate cancer.